Comparative Efficacy of Modafinil and Methylphenidate in Managing Excessive Daytime Sleepiness in Parkinson’s Disease: Results from a Randomized Controlled Trial - Kakar, Amanullah; Akbar, Wazir; Ahmed, Riaz; Kakar, Ainullah; Essa, Muhammad (Indus Journal of Bioscience Research, 2025)
Background: Excessive daytime sleepiness (EDS) is a prevalent and debilitating non-motor symptom of Parkinson’s disease (PD), yet treatment alternatives are still constrained. This study aimed to evaluate the efficacy and safety of modafinil against methylphenidate in mitigating excessive daytime sleepiness in people with Parkinson’s disease. Methods: In this double-blind, randomized, placebo-controlled trial, 110 patients with idiopathic Parkinson’s disease and an Epworth Sleepiness Scale (ESS) score of 10 or above were recruited from two neurology clinics in Quetta, Pakistan, between December 2023 and February 2025. Participants were randomly assigned to receive modafinil (200 mg/day, n = 44), methylphenidate (10–20 mg/day, n = 52), or a placebo (n = 14) for six weeks, with optional follow-up assessments at 12 and 24 weeks. The primary outcome was the alteration in the Epworth Sleepiness Scale (ESS) score at six weeks. Secondary objectives encompassed sleep quality (Pittsburgh Sleep Quality Index, PSQI), cognitive function (Montreal Cognitive Assessment, MoCA), quality of life (PDQ-39), and motor symptoms (UPDRS-III). Safety and tolerability were evaluated using adverse event surveillance. Subgroup and multivariate analyses investigated predictors of treatment response. Results: Both modafinil and methylphenidate markedly decreased ESS scores relative to placebo at six weeks (mean change: -6.6 for modafinil, -4.4 for methylphenidate against -0.3 for placebo; p < 0.001). Modafinil exhibited a significant enhancement in sleep quality (PSQI), with a substantial effect size (Cohen’s d = 0.91). PDQ-39 scores showed substantial enhancement in both active groups, especially with modafinil (mean: 35.6 compared to 48.2 in placebo; p = 0.003). Cognitive function and motor symptoms exhibited stability between groups. Adverse events occurred more frequently in the methylphenidate group (32.7%) compared to the modafinil (18.2%) and placebo (7.1%) groups, although the majority were mild to moderate in severity. Longitudinal follow-up revealed a progressive reduction in treatment efficacy. Subgroup analysis indicated enhanced advantages in people with milder disease (Hoehn & Yahr stage ≤2). The baseline ESS score and disease severity independently forecast treatment response. Conclusions: Modafinil and methylphenidate both significantly reduced excessive daytime sleepiness in Parkinson’s disease, with modafinil demonstrating enhanced efficacy and tolerance. These data suggest the prospective efficacy of modafinil as a secure and successful treatment alternative for addressing excessive daytime sleepiness in Parkinson’s disease, especially in the first phases of the disorder.